The Effectiveness of Boron Preservatives to Prevent Dry-wood Termite Attack on Mahogany Sapwood - Aryati Larasati; Joko Sulistyo (Wood Research Journal, 2014)
Mahogany wood  is utilized for many furniture products and construction purposes. The objective of this experiment was to  prevent  wood-destroying  insects  by   using  boron  preservatives  such as boric  acid  and borax.   Materials  used were mahogany  sapwood  planks  (19   years)  obtained  from   community  forest  in  Kali  Bawang  District,  Kulon  Progo.  Two preservation  methods,  i.e.,  hot-soaking  (1,   2,   and  3  hours) and  the   cold-soaking  (12,   24,   36,   and  48  hours)  in  5% concentration,  were used. The drywood termites  (Cryptotermes  cynocephalus Light)  were used for  observation.  The result showed that  the  retention  value ranges were 4.25  to 12.99  kg/m3  for cold-soaking  method and 3.09  to 9.53  kg/m3  for heat- soaking method. Mortaliy rate and mass loss  due to termite attacks ranged from  56.0  to 80.6  % (control values : 43.3%) and 850  to  1370  mg  (control values : 1930  mg). Significant interaction between soaking time and the  type of  preservative was observed to  discover its  effect on  the  levels of  retention (cold soaking) and mortality rate of  termites (hot  soaking). Boron preservatives tended to enhance the  repellent properties than  its toxicity.